Marketing Strategies and Financial Performance of Cooperatives: A Narrative Literature Review Focused on Sablayan, Occidental Mindoro - Alegre, Alberlyn Jo Mary L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This research as a narrative literature review focus on exploring the marketing strategies and financial performance of cooperatives by concentrating on the multipurpose cooperatives in Sablayan, Occidental Mindoro, which stands out as the most prevalent type of cooperative in the municipality. Through an analysis, 42 relevant and related studies both empirical and conceptual that were published within the period of 2015-2025 are explored and examined. The literatures and articles were carefully selected through a dual independent screening. A PRISMA flow diagram was used to strengthen transparency in the selection of studies to be included in the review. Moreover, the results found that marketing innovations, strong governance, technology adoption and implementation, and organizational support mold good cooperative financial performance. Also, the findings indicate the significance of marketing strategies such as product innovation, traditional approaches, and digital marketing in cooperatives good financial status. While it is recommended that continued capacity building programs shall be done for ensuring financial stability. This research offers practical lessons for cooperative leaders and policymakers, while also encouraging further empirical studies to better understand the relationship and to promote the use of digital marketing in rural cooperatives like in the province of Occidental Mindoro.